Environmental DNA metabarcoding reveals winners and losers of global change in coastal waters. Issue 1940 (9th December 2020) - Gallego, Ramón; Jacobs-Palmer, Emily; Cribari, Kelly; Kelly, Ryan P.
Abstract : Studies of the ecological effects of global change often focus on one or a few species at a time. Consequently, we know relatively little about the changes underway at real-world scales of biological communities, which typically have hundreds or thousands of interacting species. Here, we use COI mtDNA amplicons from monthly samples of environmental DNA to survey 221 planktonic taxa along a gradient of temperature, salinity, dissolved oxygen and carbonate chemistry in nearshore marine habitat. The result is a high-resolution picture of changes in ecological communities using a technique replicable across a wide variety of ecosystems. We estimate community-level differences associated with time, space and environmental variables, and use these results to forecast near-term community changes due to warming and ocean acidification. We find distinct communities in warmer and more acidified conditions, with overall reduced richness in diatom assemblages and increased richness in dinoflagellates. Individual taxa finding more suitable habitat in near-future waters are more taxonomically varied and include the ubiquitous coccolithophore Emiliania huxleyi and the harmful dinoflagellate Alexandrium sp. These results suggest foundational changes for nearshore food webs under near-future conditions.